9(a-2)=36

Simple and best practice solution for 9(a-2)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(a-2)=36 equation:


9(a-2)=36

We simplify the equation to the form, which is simple to understand
9(a-2)=36

Reorder the terms in parentheses
+(+9a-18)=36

Remove unnecessary parentheses
+9a-18=+36

We move all terms containing a to the left and all other terms to the right.
+9a=+36+18

We simplify left and right side of the equation.
+9a=+54

We divide both sides of the equation by 9 to get a.
a=6

See similar equations:

| (x+4)(4x-5)=0 | | -7+2x=-6x-71 | | 3v+1=6v-8 | | -8(2t+2)=-64 | | 20x-x^2=64 | | -23-(16-12n)+2= | | 1/3-4x1 | | 5/x+1-4/2x+2+2/2x-1=13/18 | | a+b-2ab=0 | | ln(x^3-4x)-ln(x+2)=2lnx | | 4x-20+x=90 | | x-b/b-x | | 12k+19=3k-1 | | 4/3x•3/2x= | | 1/4-9z^2 | | (-1)4= | | (6+9a)*(2a+5)= | | 9m-17=46 | | 8x=18+6x | | 3(2x-4)+8=x+6 | | 12+x-11=-11 | | 5y^4+8y^3-4y^2= | | -2xy+3xy= | | 4e+4=32 | | -6v+12=-4(v-5) | | 4(m+2.5)=7.9 | | -3x+1=-4x-4 | | 3q+6=21 | | 5x+18=-x+54 | | 1.2x+37=34.6 | | x^6-7x^3+12= | | 2k^2+5k+20=0 |

Equations solver categories